2015
DOI: 10.4236/jct.2015.68082
|View full text |Cite
|
Sign up to set email alerts
|

Protracted Adjuvant Temozolomide in Glioblastoma Multiforme

Abstract: Purpose: Radiotherapy with concurrent temozolomide (TMZ), followed by 6 cycles of adjuvant TMZ, is the standard of care for newly diagnosed Glioblastoma Mulltiforme (GBM). However tumor progression is the role with median survival of almost 14 months. With lack of effective second line chemotherapy, many physicians and some guidelines advocate prolonged use of adjuvant TMZ more than 6 months. We conduct this study to test the efficacy of protracted adjuvant conventional dose TMZ over the standard 6 doses of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…Despite the great advances in multimodality approach for high grade glioma, the optimal treatment remains a challenging issue for the oncologist. Extending the duration of adjuvant TMZ therapy has been evaluated in several studies to optimize treatment and to improve survival [5][6][7][8][9][10][11][12]. In our study, 55/121 patients (45.5%) were eligible and retrospectively analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the great advances in multimodality approach for high grade glioma, the optimal treatment remains a challenging issue for the oncologist. Extending the duration of adjuvant TMZ therapy has been evaluated in several studies to optimize treatment and to improve survival [5][6][7][8][9][10][11][12]. In our study, 55/121 patients (45.5%) were eligible and retrospectively analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, patients received up to six cycles of adjuvant TMZ therapy according to Stupp protocol (Group 1). However, survival bene t of long term TMZ administration [5,7,8,9], relative tolerability of TMZ and absence of effective second line therapies, were the important elements supporting physicians' decision to allow up to 12 cycles (Group 2) of therapy in patients with good PS (according to ECOG PS) [13] both after surgery and during follow up, manageable toxicity, stable or responsive disease according to Response Assessment in Neuro-Oncology (RANO) criteria [14]. The dose of adjuvant TMZ was 150 mg/m 2 /day for ve days in the rst cycle and increased to 200 mg/m 2 /day for ve days in the subsequent cycles if no hematologic toxicity had occurred.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, there has been little improvement in the survival outcomes of patients with newly diagnosed glioblastoma since the introduction of chemotherapy following the seminal trial results in 2005 . The justification for a definitive randomized study is that several small retrospective studies and limited randomized phase II studies have suggested that extending post‐radiation chemotherapy up to 12 cycles can improve survival, without an increase in toxicity . The small numbers of patients included in the randomized studies, as well as the multiple confounders in any unselected clinical series create concern regarding the significance of the reported findings.…”
Section: Recently Initiated and Proposed Registry‐based Rcts In Austrmentioning
confidence: 99%